Pengaruh Program Musyawarah Guru Mata Pelajaran (MGMP) dan Musyawarah Kelompok Kerja Kepala Sekolah (MKKKS) terhadap Peningkatan Kinerja Guru di Kabupaten Kutai Kartanegara - Santoso, Agus; Achmad, Andi; Wardana, Muhammad Ibnusyam (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Apathy about teacher performance in schools is one reality. The fact of the tendency of doubt about the performance of the teacher could have been caused by the absence of the development of knowledge and skills related to the four teacher competencies. On the other hand, there is still a problem regarding the lack of systematic management of school performance programs that are not managed systematically and are not in accordance with the education calendar that has been formulated and established so that in daily implementation the school is always changing, disrupting the learning process that has been determined. To overcome these obstacles a place for teachers and principals is needed that aims to gather various new information and experiences in the industrial era 4.0. The purpose of this study was to determine the effect of the Subject Teachers' Consultation and School Principal Working Groups simultaneously on Improving Teacher Performance in Kutai Kartanegara District. This type of research is a field research with a quantitative approach. Data collection techniques in this study used a questionnaire and documentation. Data validity test uses validity test, normality test and classic assumption test. Data analysis techniques using multiple linear regression test. Based on the results of the study note that there is no simultaneous effect between the Subject Teachers' Deliberation Program and the Principal Working Group Conference on Improving Teacher Performance in Kutai Kartanegara District. The absence of this influence is due to the the Subject Teachers' Deliberation Program and School Principal Working Groups in Kutai Kartanegara Regency which are considered not working properly according to the planned program. Whereas on the other hand it is considered a lack of support from stakeholders in the area, in this case the government which oversees the Subject Teachers' Deliberation Program and School Principal Working Groups. So based on data between the Subject Teachers' Deliberation Program and School Principal Working Groups, they have not synergized well.